Análise de emissões de HCT e CO de motor a diesel usando biodiesel produzido de resíduos de óleo de fritura a partir da tecnologia de plasma não térmico - Osório, Fernando da Silva (2020)
Researches for new fuel replacements petroleum diesel (petrodiesel), used in compression combustion engines, indicate biodiesel as main applicant, due his sustainability and usage possibility in energetic matrices. In this work an analysis for gases emission from a diesel compressor combustion engine (CCE) was formulate, regarding HCT emissions (%, v/v) and CO (ppm). Is applied biodiesel (B100) derivate from frying oil transesterification produced in two ways – conventional chemical catalysis and non-thermal plasma technology (PNT). By this way, three engine rotation series had emission investigated – 900, 1500 and 2500 rpm, comparing equal tests realized using biodiesel obtained for chemical transesterification catalysis of frying residual oil and conventional road diesel S-500, acquired from gas station without biodiesel adds. The blends (proportion mixes) uses as base S-500 and B100 prepared by 15 and 30 PNT minutes at 2, 12, 20 and 50% biodiesel volume with S-500. Those diesel engine application mixes of S-500 and biodiesel with 15 and 30 minutes of PNT showed reduction efficiency in HCT and CO indexes allied 62% and 80% reductions, respectively, comparing emissions taking only S-500. Frying biodiesel oil shown his emissions efficiency with low CO and HCT levels, emphasizing reductions in biodiesel from PNT technology produced.